On the turn-around phenomenon in n-MOS transistors under NBTI conditions. (July 2016) - Benabdelmoumene, A.; Djezzar, B.; Chenouf, A.; Tahi, H.; Zatout, B.; Kechouane, M.
Highlights: NBTI investigation in n-MOSFET using current–voltage and charge pumping techniques. Turn-around phenomenon in threshold voltage shift and maximum charge pumping current. NBTI-induced progressive trap creation: from interface to near interfacial oxide region. Abstract: We have experimentally analyzed negative bias temperature instability (NBTI) stress/recovery cycle on n-channel metal oxide semiconductor field effect transistors (n-MOSFET's). Data obtained by current–voltage ( I – V ) and charge pumping ( CP ) techniques have revealed a turn-around phenomenon in both threshold voltage shift (Δ Vth ) and maximum CP current shift (Δ ICP-Max ). This allows us to separate the evolution of interface traps (permanent) and near interfacial oxide traps "border traps" (recoverable) as a function of the stress time. The ability of separation comes from the fact that interface and oxide traps induce opposite shifts in Δ Vth . Contrarily to NBTI/n-MOSFET, NBTI/p-MOSFET is unable to achieve trap separation because both trap types induce shifts in the same direction. Exploiting the turn-around effect, we have been able to follow the evolution of the degradation over the stress time. NBTI stress/relaxation cycle CP measurements on n-MOSFET have shown a progressive creation of traps; starting from the interface traps to near interfacial traps. This new and simple procedure will give a deeper insight into the dynamics of traps build up under NBTI conditions.